Homicidal Poisoning in China Using Several Anesthetic Drugs. Issue 3 (29th February 2016) - Ye, Yi; Yan, Youyi; Gong, Daoyin; Guo, Run; Yang, Lin; Liao, Linchuan
Abstract: The authors describe a case of a well‐designed homicidal poisoning in China. A male was treated with starvation, intravenous fluids and antibiotics while in the hospital for acute diarrhea. He suddenly suffered from shortness of breath and subsequently died. A forensic autopsy was carried out, and several specimens were collected for toxicological screening. Propofol was tentatively identified in the blood by GC‐MS. Based on the presence of propofol in the blood, a suspect confessed that two other drugs, namely midazolam and vecuronium, were involved in this murder. Analytical drug quantification was then performed by GC‐MS and LC‐MS/MS. Blood analysis revealed the following: propofol at 0.5 μg/mL, midazolam at 0.098 μg/mL, and vecuronium at 0.10 μg/mL. These results suggest that the cause of death was respiratory depression due to the acute combined effect of several anesthetic drugs administered by the victim's companion.